The foot in the history of English: challenges to metrical coherence - Dresher, BE; Lahiri, A (John Benjamins Publishing Company, 2022)
Dresher & Lahiri (1991) propose that Old English displays ‘metrical coherence’: different phonological processes are sensitive to the same metrical structure. We consider how English has dealt with challenges to metrical coherence. We show that the resolved moraic trochee, assumed to characterize the early Old English foot (Bermúdez-Otero manuscript; Goering 2016a, b), became untenable after the shortening of unstressed vowels, arguing that this stage of Old English, at least, requires the Germanic Foot, an extended and resolved trochee. After 1570 (Lahiri 2015) the direction of parsing changed from left-to-right to right-to-left when the number of Latin loanwords with stress-affecting suffixes had passed a threshold derived from Yang’s Tolerance Principle (Yang 2016). This change reestablished the metrical coherence that had been disrupted by these words.